Maine's Public Interest Groups: The Industrial Energy Consumers' Group - Staff, Editorial (Maine Policy Review, 1993)
The actors in public policy include not only elected and appointed public officials, but also the public interest groups that promote various agendas. To help understand the perspectives of some of these groups, Maine Policy Review plans to profile Maine's public interest groups in each issue, featuring in this article the Industrial Energy Consumer’s Group (IECG).
Keywords: industrial energy; Maine Industrial Energy Consumer’s Group